Literature Review on the Need to Develop Behaviour Based Safety (BBS) Guide Note for Small and Medium Manufacturing Companies (SMI) In Malaysia - Zulkifly, Syazwan Syah; Harith, Siti Hawa (UUM, 2022)
Small and Medium Enterprises (SMEs) contribute to at least 70% of workplace accidents in Malaysia. Financial and human resource limitations have been found to be the main causes and a tailored approach is needed to overcome the problem. Previous literature has revealed that unsatisfactory safety behaviour is the leading cause of workplace accidents and Behaviour-Based Safety (BBS) program has been identified as the most effective solution. This study aimed to determine the level of safety behaviour amongst the SME manufacturing workers in Malaysia and the necessity of establishing a guide note or guidelines for implementing BBS for the specific use of the SME manufacturing firms (SMI). Systematic literature review method has been utilised in this study and the results affirmed the need of developing a guide not for BBS tailor to the SMI, due to their limitations and financial constraints whereby the existing BBS programs are more suitable to huge firms with plenty of resources. In conclusion, an emperically and theoretically driven BBS guide note for SMI is proposed to be design and developed by the Department of Occupational Safety and Health to serve as a guide for Malaysia’s SME manufacturings in conducting BBS program.